Ideas, interests, and the tipping point: economic change in India - Mukherji, Rahul (Review of international political economy, 2012)
This paper makes the case for a ‘tipping point’ model for understanding economic change in India. This gradual and largely endogenously driven path calls for the simultaneous consideration of ideas and politics. Exogenous shocks affected economic policy, but did not determine the course of economic history in India. India's developmental model evolved out of new ideas Indian technocrats developed based on events they observed in India and other parts of the world. A historical case for the ‘tipping point’ model is made by comparing two severe balance of payments crises India faced in 1966 and 1991. In 1966, when the weight of ideas and politics in India favored state-led import substitution, Washington could not coerce New Delhi to accept deregulation and globalization. In 1991, on the other hand, when Indian technocrats’ ideas favoured deregulation and globalization, the executive-technocratic team engineered a silent revolution in the policy paradigm. New Delhi engaged constructively with Washington, making a virtue of the necessity of IMF conditions, and implemented a home-grown reform program that laid the foundations for rapid economic growth in world's most populous and tumultuous democracy.
Gesehen am 11.12.2017